Impact of the introduction of pneumococcal conjugate vaccine on rates of community acquired pneumonia in children in northeast Brazil (Research, Society and Development, 2020)
Evaluating the impact of the 10-valent pneumococcal conjugate vaccine on the hospitalization of children under five years of age before and after its implementation in the city of Patos, PB – Brazil. The first part of this paper comprises a descriptive study with a transversal approach; the data were collected through scrutiny of the patients’ hospital records. For that effect, every medical record found from 2005 until 2015 (periods before and after the introduction of the PVC10 to the Brazilian vaccination schedule) were examined, the ones diagnosed with pneumonia were selected and those that belonged to children from Patos were analysed. The second part includes an ecological time series, whose data were collected from the Paraiba State 6thRegional Health Section database to access information from the National Immunization Program Information System (NIP-IS). It has been found that there were 1,094 hospitalizations for pneumonia on children under 5 years of age within the ten-year-period investigated. The data confirm a declining tendency of hospital admissions for pneumonia in the city of Patos-PB in the analyzed time series, and the PVC10 vaccination coverage has been effective in the analyzed municipality. Despite the declining tendency, the number of cases is still considerably high. Being aware that in the health-disease process children’s hospitalizations are caused by multiple variables including social, economic and cultural issues, it is fundamental the establishment of public policies as well as active surveillance that continuously evaluates the profiles and occurrences of pneumonia cases in Brazil.